Effectiveness of collaborative language tasks in language teaching and learning / Siu-lun Lee and Yongyin Chen - Chen, Yongyin (2013)
This paper focuses on the application of collaborative language tasks in classrooms teaching Cantonese as a second language in Hong Kong. An action research was carried out in a Cantonese classroom in Hong Kong. In this research, eighty beginning adult learners from different countries were studied for ten weeks. Classroom observation, questionnaires and interviews were used to look at learners’ views about using collaborative tasks in language classrooms. Questionnaires and interviews results show that students have positive views about collaborative tasks. Classroom observation data show that students have made use of communication strategies, such as probing for additional information and rephrasing of questions in order to finish the tasks.